Metatranscriptomic identification of novel RNA viruses from raccoon dog (Nyctereutes procyonoides) feces in Japan - Oba, Mami; Sakaguchi, Shoichi; Teshima, Natsuko; Yokota, Tomoko; Takemae, Hitoshi; Tohei, Mao; Shimokawa, Fumie; Murakami, Masaru; Mizuno, Shuntaro; Ishida, Hiroho; Murakami, Hironobu; Takano, Tomomi; et al. (Scientific reports, 2025)
The raccoon dog ( Nyctereutes procyonoides ), classified in the order Carnivora within the family Canidae , is native to East Asia and widely distributed throughout Japan due to its adaptability to various environments. Despite the close relationship between raccoon dogs and other animals, viruses infecting raccoon dogs have not been thoroughly investigated in Japan. In this study, we performed metatranscriptomic analyses using fecal samples collected from latrines of wild raccoon dogs in two locations on mainland Japan. Nearly complete viral genomes were identified, including viruses belonging to the genus Kobuvirus (CaKoV), an unclassified canine sapelovirus within the subfamily Ensavirinae (CaSaV), the Genius Mamastrovirus (CaAstV), unclassified hepe-astro-like virus (bastrovirus-like) (Bast-like V), and an unclassified dicistrovirus (DiciV) within the family Dicistroviridae . Phylogenetic analyses revealed that raccoon dog CaKoV, CaSaV, and CaAstV are related to canine strains but form independent clusters specific to raccoon dogs, suggesting they have evolved within this host population. Bast-like V, detected for the first time in raccoon dogs, showed high sequence identity with viruses previously identified in Chinese shrews. The shared insectivorous nature of these hosts and in silico host range predictions suggest that Bast-like Vs may originate from arthropod viruses. Although DiciV is likely of dietary origin due to its arthropod hosts, the large number of sequence reads detected and the phylogenetic clustering of raccoon dog DiciVs with mammalian DiciVs indicate the need to assess their potential infectivity in mammals and the risk of spillover. These findings suggest that raccoon dogs harbor endemic viruses within the canine population and may act as potential vectors for viruses with unknown infectivity in mammals but with spillover risk.